A Study On The Relationships Between Individual And Organisation Career Management Practices Toward Academics’ Career Success - Tee, Poh Kiong (2021)
The private higher education sector in Malaysia has grown tremendously, but a huge decline has been observed in its number of academic staff members. This issue has drawn considerable attention from the industry and the government, who have raised concerns about academics’ career status, particularly their career opportunities and success. This research sought to investigate academics’ career success factors by taking a more convergent view of the impact of both individual and organisational factors through the lens of contemporary career management. The mediating role of perceived employability was examined in this relationship by distinguishing between perceptions of internal and external employability. Data from 288 academics in Malaysian private universities was collected and analysed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings revealed that a protean career attitude has no significant direct influence on career success; rather, it has an indirect effect on career success via perceived internal and external employability. Organisational learning practices have a significant direct and indirect influence on career success. Both internal and external perceived employability mediate the effects of a protean career attitude iii and organisational learning practices on career success, with perceived external employability having a stronger direct and mediating effect on academics’ career success. This study uncovers that Malaysian academic staff depend upon external employment opportunities to pursue success in academia. Since perceived external employability has the greatest impact on academics’ career success, universities should retain their academics and remove them from the external labour market by focusing on the learning and development strategies that bind employees to the organisation. The results are particularly meaningful for stakeholders in the higher education sector in relation to the effective management of academic staff to create a sustainable advantage in the age of the internationalisation and commercialisation of the higher education industry. The implications of the findings are discussed along with the study’s limitations and future research directions